Memoria, discurso y narrativas en la propaganda política (1980-2000) - Arce Plasencia, Óscar Gabriel (2021)
In Peru, historical memory is a concept that has sparked many debates in relation to its role as a legitimizing element of our identity. This is due to the different ways that recovering the past implies, because it prioritizes certain memories to the detriment of others. This is evident in a notorious way during the twenty years of armed conflict (1980-2000) and the antagonistic political speeches given in it. Therefore, in order to better understand the role of memory during this period, this research seeks to identify how it is used in the political propaganda made or attributed to the two most important political leaders of that conjuncture: Abimael Guzmán and Alberto Fujimori. In this way, it seeks to approach the term from a more tactical perspective in which both leaders use historical memory for the construction of narratives for various political purposes. To identify them, a coding and subsequent categorization of the information found was made. The chosen propaganda pieces were grouped according to five milestones associated with each of the actors to be analyzed. As a result, nineteen uses of memory were found, with a greater incidence in Alberto Fujimori, because he had greater multimedia access unlike Abimael Guzmán, who also used to reinforce certain narratives, instead of renewing them. However, it was also possible to see that both characters share twelve of the established uses, especially those associated with the pejorative, the exaltation, the disruption and, mainly, the vindication.